Análise do consumo energético de forno elétrico a arco voltaico utilizado em indústria metalúrgica nacional - Diniz, Patrícia Helena de Assis [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The necessity of remaining competitive, by reducing costs and increasing productivity while simultaneously improving quality, has led the steel industry to seek transformations aimed at continuously improving the manufacturing process of liquid steel. In this context, the concept of energy consumption and consumption of inputs has been studied in recent years, mainly in papers that demonstrate technological advances in the steelmaking process in Electric Arc Furnaces (EAF). There is a large variation of total energy consumed in EAFs, being measured in the primary side of the transformer, the reason is the use of different technology processes. The use of oxygen in the process brings great benefits both in the removal of some disposable chemical elements and in the reduction of the consumption of electric energy. Therefore, since the steel mills use different proportions of electrical and chemical energies, it is relevant to discuss energy consumption. The present final paper considered the influence of parameters in the electric circuit affecting the consumption of inputs and in the energy consumption, besides the proof that the quantity of loads and fluxes in the EAF influences in the increase of the electric energy consumption

A necessidade de permanecer em condições de competitividade, mediante a redução dos custos e do aumento da produtividade com a simultânea melhoria da qualidade, tem feito com que as indústrias siderúrgicas buscassem transformações que objetivam a melhoria contínua do processo de fabricação do aço líquido. Nesse contexto, o conceito de consumo de energia e consumo de insumos têm sido muito estudados nos últimos anos, essencialmente em trabalhos que evidenciem avanços tecnológicos do processo de fabricação do aço em Fornos Elétricos a Arco (FEA). Existe grande variação de energia total consumida em FEAs, sendo medida no transformador primário, por processos utilizando diferentes tecnologias. A utilização da ingestão de oxigênio no processo, traz grande benefício tanto na remoção de alguns elementos químicos indesejáveis quanto na redução do consumo de energia elétrica. Portanto, desde que as aciarias utilizam de diferentes proporções de energias elétricas e químicas, é relevante discutir o consumo de energia. O presente trabalho considerou a influência de parâmetros no circuito elétrico afetando no consumo de insumos e no consumo energético, além da comprovação de que a quantidade de carregamentos e fundentes no FEA influencia no aumento do consumo de energia elétrica
Energy consumption analysis of electric arc furnace used in national metallurgical industry
Keywords: Produtividade; Fornos elétricos; Indústria siderúrgica - Custo; Costs